Integrating the Qur’ān Verses into Secondary School Science Curriculum of Yemen: An Islamic Perspective - Al-Hadabi, Abdulsalam Sulaiman Dawood (International Journal of Humanities and Social Science Research, 2016)
This study attempted to answer the following questions: "(1) What are the Qur’ān Verses (QVs) that are suitable to be integrated into Secondary School Science Curriculum of of Yemen (YSSSC)? And (2) "In what neutral sciences disciplines (NSDs) of YSSSC these verses can be integrated? To this end, Delphi technique-two rounds (i.e. DTRI and DTRII) as well as interview were used to collect data from ten panelists. Panelists were selected based on two criteria: specialization and level of education. Each of panelists was either professor or assistant professor at Yemeni universities. Panelists were asked to give their own perspectives on the suitability of the QVs for integrating in YSSSC and to give their perspectives in which NSDs these verses could be integrated. A constructed questionnaire consisted of 200 QVs was used to carry out DTRI and DTRII, too. Result of DTRI was 161 of 200 QVs, while all 210 QVs of the DTRII' questionnaire were accepted as a suitable QVs to be integrated in YSSSC. In addition, the suggested QVs were decreasingly distributed (i.e. the highest first, then the lowest) among the NSDs of YSSSC as follows: environment, biology, chemistry, astronomy, physics, and earth. Based on the results of this study, it is recommended that Integrated Qur’ān-science approach might be Yemeni school curricula-based (i.e. science curricula).